Extradigital glomus tumor as a cause of chronic perianal pain - Rathi K; Jena J; Dash B; Mitra D; Patnaik P; Basu A (Wolters Kluwer Medknow Publications, 2009)
Glomus tumor is a rare perivascular benign tumor arising from the Sucquet-Hoyer canal of the normal glomus body, most commonly in the digital areas. We report a serving soldier with such a tumor in an atypical site, the perianal region, presenting with episodic shooting pain. Total surgical excision was performed. Histopathology revealed a well-circumscribed tumor composed of clusters of monotonous polygonal cells surrounding capillary-sized blood vessels. Tumor cells also showed immunopositivity for smooth muscle antigen and vimentin. Following excision, the patient was completely relieved of pain and there was no recurrence on follow-up for 6 months.